2021
DOI: 10.1093/jac/dkab367
|View full text |Cite
|
Sign up to set email alerts
|

Dolutegravir-based dual maintenance regimens combined with lamivudine/emtricitabine or rilpivirine: risk of virological failure in a real-life setting

Abstract: Background Maintenance ART with dolutegravir-based dual regimens have proved their efficacy among HIV-1-infected subjects in randomized trials. However, real-life data are scarce, with limited populations and follow-up. Objectives We assessed virological failure (VF) and resistance-associated mutations (RAMs) on dolutegravir maintenance regimens in combination with rilpivirine or with lamivudine or emtricitabine (xTC) and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In general, INSTI mutations were infrequently detected at VF across studies identified in this review, even in cohorts where individuals had previous VF and/or historical mutations. VF rates ranged from 1% to 60% among the 16 lead studies reporting VF outcomes [33,[36][37][38][39][40][41][42][43]45,46,49,50,53,58,59] for individuals on DTG-based regimens (excluding 8 lead studies with 100% VF rates due to study design [31,32,35,44,48,52,60,62], i.e., resistance analyses in populations failing treatment); of note, the highest rates (50% and 60%) were observed in cohorts with N ≤ 5 [53,58]. These results are consistent with other real-world studies [69][70][71] reporting low VF rates and/or infrequent INSTI RAM development in people receiving DTG-based treatment and reinforce the high barrier to resistance observed in interventional studies in ART-naive and ART-experienced individuals [14][15][16][17][18][19][20][21][22][23][24][25]27,…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, INSTI mutations were infrequently detected at VF across studies identified in this review, even in cohorts where individuals had previous VF and/or historical mutations. VF rates ranged from 1% to 60% among the 16 lead studies reporting VF outcomes [33,[36][37][38][39][40][41][42][43]45,46,49,50,53,58,59] for individuals on DTG-based regimens (excluding 8 lead studies with 100% VF rates due to study design [31,32,35,44,48,52,60,62], i.e., resistance analyses in populations failing treatment); of note, the highest rates (50% and 60%) were observed in cohorts with N ≤ 5 [53,58]. These results are consistent with other real-world studies [69][70][71] reporting low VF rates and/or infrequent INSTI RAM development in people receiving DTG-based treatment and reinforce the high barrier to resistance observed in interventional studies in ART-naive and ART-experienced individuals [14][15][16][17][18][19][20][21][22][23][24][25]27,…”
Section: Discussionmentioning
confidence: 99%
“…The proportions of people living with HIV who experienced VF on DTG-based therapy and developed treatment-emergent integrase mutations by study and regimen are shown in Table 1. While the definition of VF varied, many included 1 or 2 consecutive measurements of "detectable" HIV-1 RNA [31,32], or 1 or 2 consecutive measurements of HIV-1 RNA > or ≥50 copies/mL [33][34][35][36][37][38][39][40][41], >200 copies/mL [40,42,43], >400 copies/mL [37,44], ≥500 copies/mL [41], and/or >1000 copies/mL [45,46] as part of study-defined VF criteria. Many did not explicitly define VF criteria [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62].…”
Section: Treatment-emergent Resistance By Regimenmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for dolutegravir (DTG) plus lamivudine (3TC) treatment in persons with past 3TC resistance is limited and comes mostly from retrospective cohorts or small prospective studies showing, so far, that past M184V/I mutations do not have a significant negative impact on maintenance of virological suppression and that, when virological failure occurs, it does not involve emerging integrase resistance [ 1–4 ].…”
mentioning
confidence: 99%
“…The availability of effective 2-drug combinations has made it possible to reduce cumulative drug exposure, long-term toxicity, risk of drug–drug interaction, and costs of antiretroviral regimens. 3,4 However, an unsolved question about dual therapies is the risk of an incomplete virological suppression in viral reservoirs, leading to a significant residual viremia and a persistent inflammatory state. In clinical trials, the dual combination dolutegravir/lamivudine has demonstrated a durable and noninferior virological efficacy in comparison with 3- and 4-drug regimens in both antiretroviral therapy–naive and antiretroviral therapy–experienced patients, but data about the anti-inflammatory effects of current dual regimens are still scarce.…”
mentioning
confidence: 99%